2019
DOI: 10.1097/pec.0000000000001971
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Foreign Body Imaging Using Point-of-Care Ultrasonography

Abstract: The ingestion of foreign bodies is a common problem in the pediatric population. Emergent treatment of ingested foreign bodies is dependent on the type of foreign body ingested, patient symptoms, timing of ingestion, and the location of the foreign body. Although X-ray and computed tomography are the imaging techniques used most often to assess for foreign bodies, ultrasonography, which lacks ionizing radiation, may also be useful. This case series describes 8 cases of gastrointestinal tract foreign bodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…24 This review depicts as precisely as possible the different PoCUS procedures reported in the case of FBI in the included articles. 7,[9][10][11][12][13][16][17][18]20 Some of these studies also proposed a PoCUS protocol to evaluate FBI patients, which consisted of an upright and slightly forward tilting position with a stomach filled with water. [9][10][11]18,20 One study additionally describes a teaching method to acquire the necessary skills in PoCUS evaluation for FBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This review depicts as precisely as possible the different PoCUS procedures reported in the case of FBI in the included articles. 7,[9][10][11][12][13][16][17][18]20 Some of these studies also proposed a PoCUS protocol to evaluate FBI patients, which consisted of an upright and slightly forward tilting position with a stomach filled with water. [9][10][11]18,20 One study additionally describes a teaching method to acquire the necessary skills in PoCUS evaluation for FBI.…”
Section: Discussionmentioning
confidence: 99%
“…In the 52 FBI cases reported in the 14 identified articles, all FB were correctly identified and localized using PoCUS. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] In 5 cases (8.5%), PoCUS was used as the only diagnostic modality 7,11 out of which 3 (60%) underwent a successful procedure to remove the FB 11 and 2 (40%) received a conservative treatment without complications. 7,11…”
Section: Diagnostic Accuracy Of Pocus For Identification Of Fbimentioning
confidence: 99%
“…However, it appears to be a valuable tool in different gastrointestinal and abdominal conditions in both the elective and the emergency setting [13]. Recent studies have shown that US can be useful even for evaluating foreign bodies (FBs) in the gastrointestinal tract and identifying associated complications [14][15][16]. The role of pediatric Point-Of-Care Ultrasound (POCUS) for detection of FBs (mainly esophageal and gastric) in the emergency departments is becoming more and more relevant as it may assist clinicians integrating the clinical examination with real-time images before using more time-and resource-consuming techniques [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sonography can be used to locate both radio‐opaque 1 and radio‐lucent 2 foreign bodies in the gastrointestinal tract. While a wooden toothpick would be expected to be isoechoic to moderately hyperechoic, fluid absorption over time may have increased echogenicity in our case.…”
Section: Discussionmentioning
confidence: 99%